Gut microbiome and reproductive endocrine diseases: a Mendelian randomization study - Liang, Ye; Zeng, Weihong; Hou, Tao; Yang, Haikun; Wu, Boming; Pan, Ru; Huang, Lishan (Frontiers in Endocrinology, 2023)
Background Observation studies have confirmed the association between the gut microbiome and reproductive endocrine diseases (REDs), namely, polycystic ovary syndrome (PCOS), endometriosis, and female infertility. However, their association has never been confirmed by a two-sample Mendelian randomization (MR) analysis. Methods We conducted a two-sample MR analysis to evaluate the relationship between the gut microbiome and the three aforementioned REDs. In order to get more comprehensive results, two different thresholds were adopted to select instrumental variables (IVs): one was a locus-wide significance threshold (P <1.0×10–5) and the other was a genome-wide significance level (P< 5×10-8). Summary-level statistics for the gut microbiome and REDs were collected from public databases. Inverse-variance weighted (IVW) was the main method used to estimate causality, and sensitivity analyses were conducted to validate the MR results. Results At the locus-wide significance level, we identified that the genera Streptococcus (OR=1.52, 95%CI: 1.13-2.06, P=0.006) and RuminococcaceaeUCG005 (OR=1.39, 95%CI: 1.04-1.86, P=0.028) were associated with a high risk of PCOS, while Sellimonas (OR= 0.69, 95%CI: 0.58-0.83, P=0.0001) and RuminococcaceaeUCG011(OR=0.76, 95%CI: 0.60-0.95, P=0.017) were linked to a low PCOS risk. The genus Coprococcus2 (OR=1.20, 95%CI: 1.01-1.43, P=0.039) was correlated with an increased risk of female infertility, while Ruminococcus torques (OR=0.69, 95%CI: 0.54-0.88, P=0.002) were negatively associated with the risk of female infertility. The genera Olsenella (OR= 1.11, 95%CI: 1.01-1.22, P=0.036), Anaerotruncus (OR= 1.25, 95%CI: 1.03-1.53, P=0.025), and Oscillospira (OR= 1.21, 95%CI: 1.01-1.46, P=0.035) were linked to a high risk of endometriosis. However, the results showed that the gut microbiome did not possess a causal link with REDs risk based on the genome-wide significance level. Sensitivity analyses further confirmed the robustness of the MR results. Conclusion Our study provides evidence that gut microbiome is closely related with REDs. Subsequent studies should be conducted to promote microbiome-orientated therapeutic strategies for managing REDs.